Comparative analysis of maize (Zea mays) hybrids under different methods of planting in spring season - KUMAR, AASHISH; KAMBOJ, B R; THAKRAL, S K (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted in Yamunanagar district of Haryana during spring 2015 to study the performance of maize (Zea mays L.) hybrids under different methods of planting in spring season. The five maize hybrids, i.e. HM-4, HM-9, HM-10, HM-11 and HQPM-5 were tested under three planting methods, viz. ridge, flat and furrow methods with three repeats. The yield attributing characters like cob length, number of grains/cob, grain weight/cob, cob weight/plant and 100 grain weight were found higher under ridge method of planting than flat and furrow methods. The grain yield, stover yield, biological yield, net returns and benefit cost ratio were also recorded higher under ridge method of planting than the other methods, whereas the yield attributing characters, yield, gross returns, net returns and benefit cost were observed higher in hybrid HM-10 over other hybrids grown in the field.